From Cognitive Assessment to Holistic Evaluation - Slamet Muhamad Susanto; Rizki Wulandari; Ade Rosade (FASHLUNA, 2026)
This study aims to describe the implementation of Islamic Religious Education (IRE) learning evaluation from the perspective of improving learning quality in Grade IV at Madrasah Ibtidaiyah Nurul Huda Sri Mulyo. The research employed a descriptive qualitative approach with research participants consisting of the Grade IV Islamic Religious Education teacher, Grade IV students, and the madrasah principal. Data were collected through observation, interviews, and documentation. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The trustworthiness of the data was ensured through source triangulation, technique triangulation, member checking, and peer debriefing. The findings revealed that the planning of learning evaluation had been carried out systematically through the preparation of lesson plans, semester programs, annual programs, and test blueprints. However, the evaluation planning was still predominantly focused on the cognitive domain, while affective and psychomotor assessments had not been optimally designed. The implementation of evaluation covered cognitive, affective, and psychomotor aspects through daily tests, assignments, attitude observations, and worship practices. Several challenges were identified, including limited time, subjectivity in attitude assessment, and inconsistencies in the implementation of practical evaluations. The results also indicated that most students had achieved the Minimum Mastery Criteria (MMC), with 27% categorized as excellent, 40% as good, 20% as fair, and 13% as poor.